ANALISIS YURIDIS PUTUSAN PENGADILAN NEGERI KABUPATEN TULUNGAGUNG NOMOR REGISTER 18 / PDT.G / 2018 / PN TLG TENTANG SENGKETA HAK ATAS TANAH EKS HAK EIGENDOM YANG BELUM DIKONVERSI: JURIDICAL ANALYSIS OF DECISION OF TULUNGAGUNG DISTRICT COURT REGISTER NUMBER 18 / Pdt.G / 2018 / PN TLG CONCERNING DISPUTES ON LAND RIGHTS EX EIGENDOM RIGHTS THAT HAVE NOT BEEN CONVERTED - Al Amin, Syauqi; Tamsil, Tamsil (NOVUM : JURNAL HUKUM, 2019)
An issue involving a civil rights council against the Bolorejo village government in the court of tulungagung district registration number 18/Pdt.G/2018/PN TLG is an example of an unlawful act perpetrated by the Bolorejo village government. This is because the government of the Bolorejo village wants to take control and use the mountain bolo hill area located in Bolorejo village, by Kauman district, tulunggreat district, as a tourist resort, which can provide an interest and icon for Bolorejo village. But the goal of developing the tourist area has been deemed illegal due to the use of the mountain bolo hill area which is a legitimate burial site on behalf of a true community. The status of the land in the foothill of mount bolo still as eigendom vorponding, is the reason government of the Bolorejo village used the cemetery as a tourist resort without first applying permission to the established peace association and holding the rights of the former western right since 1912.